Dilating venous disease: Pathophysiology and a systematic aspect to different vascular territories. (June 2016) - Yetkin, Ertan; Ileri, Mehmet
Abstract: Venous disease is a common but overlooked clinical problem and is an important mortality and morbidity factor depending on the effected vascular territory. Different contributing factors play role on the clinical manifestation of the disease. Peripheral varices of lower extremities, hemorrhoids, varicoceles, pelvic varicose veins are the vasculopathy of veins running toward heart but against gravity. We hypothesize that all these clinical entities share common pathophysiologic steps in terms of vascular wall remodeling and vessel wall damage. A systematic approaches to both arterial and venous dilating disease in further studies and research would increase our understanding on the pathophysiology of dilating vascular disease and would provoke to find out new treatment modalities. Varicose remodeling of veins occurs by a complex interplay of various factors including both physical forces and extracellular matrix remodeling mechanisms. This article focuses on the systematic aspects of dilating venous disease with a focus on pathophysiology under the term of "Dilating Venous Disease".